REGULATORY T CELLS AND THEIR ROLE IN RHEUMATIC DISEASES: A POTENTIAL TARGET FOR NOVEL THERAPEUTIC DEVELOPMENT - Diana Milojevic; Khoa D. Nguyen; Diane Wara; Elizabeth D. Mellins (Amaltea Medical Publishing House, 2009)
Regulatory T cells have an important role in limiting immune reactions and are essential regulators of selftolerance. Among them, CD4+CD25high regulatory T cells are the best-described subset. In this article, we summarize current knowledge on the phenotype, function, and development of CD4+CD25high regulatory T cells. We also review the literature on the role of these T cells in rheumatic diseases and discuss the potential for their use in immunotherapy